(3bQI GdYjf aj GdaJM hGdEeGdI Hjf GddaXjfs - (3GHf GdbGUM, Ydj Hf YKeGf Hf eMeO, J (B801 (3g`s ((3HQhSIs)
(3ChdgG (B:s
(3HYO GdHSedI ; bGd CHh GdHbG Ydj Hf YKeGf Hf eMeO Hf CMeO Hf GdMSjf GdbGUM GdYPQj CeG HYO MeOG ddg QH GdYGdejf aEf gPg GdQSGdI SejJgG bQI GdYjf hLeYJ ajgG GdeTghQ ef GdaJM hGdEeGdIs
(3BNQgG (B:s
(3ShQI GdfGS HQH GdfGS edc GdfGS Edg GdfGS UOhQ GdfGS hGdfGS LedI NeS cdeGJ PcQf HGdHbQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B4 / 311s
(3eYLe GdeDdajf (B2 / 475s
(3cTa GdXfhf (B2 / 1325s
(3gOjI GdYGQajf (B1 / 727s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdbQGAGJ hGdJLhjOs